Rocket Stove Sebagai Media Alternatif Pembakaran Sampah di Desa Selasari Kecamatan Parigi Kabupaten Pangandaran - Fadli, Fatih Zidan Nur (SENTRI: Jurnal Riset Ilmiah, 2025)
Waste management in Banjarsari Hamlet, Selasari Village, Parigi District, Pangandaran Regency remains a concern due to limited waste collection and processing facilities. Some residents still burn waste along roadsides, potentially causing smoke and increasing the risk of fire spreading. This program aimed to implement a Rocket Stove as an alternative low-smoke waste-burning facility and promote community empowerment in waste management. The program employed a descriptive qualitative approach using the Asset Based Community Development (ABCD) framework. Data were collected through observation, interviews, documentation, and field observation during the program. The results showed that the Rocket Stove provided a more directed alternative for waste burning and received positive responses from the community and local authorities. Through socialization, demonstrations, and hands-on practice, residents gained knowledge about using the Rocket Stove as an appropriate technology. The program not only produced a waste-burning facility but also encouraged community participation in waste management. Its sustainability requires continued community participation and support from local authorities.